Popular culture: it's ok to be gay! / Noor Mayudia Mohd Mothar, Siti Hajar Abd Aziz and - Mohd Mothar, Noor Mayudia; Abd Aziz, Siti Hajar; Ridzuan, Abdul Rauf (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2011)
Media in the postmodernist era are closely related to the rise of multicultural theories. One of the most important multicultural theories of today’s social world is the queer theory. Queer theory involves a range of intellectual ideas rooted in the contention that identities are not fixed and stable and do not determine who we are. It is apparent that today’s media based their concept upon this idea, as more entertainment shows from the West especially are open in discussing homosexual issues. Many people especially young people are more open to this concept. The media is in a way educating the public to accept others as what or whom they chose to be. Thus, this paper’s purpose is to analyze popular television series ‘Glee’ on how it is dealing with teen homosexuality issues.